ChatGPT Usage for Academic Purposes and Influencing Factors Among Students at Hanoi Medical University, Vietnam - Kieu, Luu Thi Thu; Vinh, Phan Huu; Mai, Nguyen Thi; Linh, Trinh Khanh; Dai, Tran Xuan; Hanh, Tran Ngan; Linh, Nguyen Ngoc; Hang, Le Thanh; Giang, Hy Minh; Anh, Vu Thi Phuong; Thanh, Pham Cong; Son, Dang Cong; Dat, Le Minh (Knowledge Dynamics, 2025)
Background: The advancement of artificial intelligence (AI) has unveiled numerous opportunities in medical education, with ChatGPT emerging as a prevalent learning support tool. However, the adoption rate and the determinants associated with the integration of ChatGPT among medical students remain under-researched. Methods: A cross-sectional study was conducted on 335 medical students at Hanoi Medical University. Data was collected using an online questionnaire in KoboToolbox, employing a convenience sampling method. The data was analyzed using Stata 17.0, employing descriptive statistics and multivariate logistic regression to examine the relationship between demographics, knowledge, and attitudes toward ChatGPT. Results: The results showed that 73.4% of students had used ChatGPT, with 68.7% using it to complete assignments and 61% believing that the tool helped save time and effort. However, only 17.9% were aware of ChatGPT's limitations. Positive knowledge and attitudes towards ChatGPT increased the likelihood of using the tool. Students with a good academic performance level were 3.25 times more likely to use ChatGPT than excellent students (OR=3.25; p=0.013), and the Dentistry department had the highest usage rate, 4.53 times higher than the General Medicine department. Conclusion: Medical students use GPT chat at a comparatively high rate. Integrating this tool into medical education requires specific guidelines to maximize benefits while ensuring accuracy and ethics.